SENGKETA JAMINAN TANAH PADA AKAD RAHN (STUDI KASUS KSPPS NURI JATIM CABANG PASONGSONGAN) - Abdul Bari; Matnin; Ahmad Syafi’i; Ahmad Nuruddin Hasbullah (DPPM Universitas Pelita Bangsa, 2023)
KSPPS NURI JATIM Pasongsngan Branch is a sharia-based savings and loan cooperative that provides various products, mudharabah, murabahah, musyarakah, wadiah, and Ar-rahn. Geographical factors that require people to do business make Ar-Rahn's products the most attractive to members, because Ar-Rahn will prepare financing funds on the condition that members bring valuable items, such as motorbike/car BPKB, land certificates, and also gold , as collateral for the financing. Therefore the purpose of writing this article is to find out the service mechanism, prevention efforts, and ways to resolve disputes between members and cooperatives. The method used is a descriptive qualitative method obtained from books, journals, and interviews with employees of KSPPS NURI JATIM, Pasongsongan Branch. The results obtained were that in preventing disputes using character analysis and economic ability as evidenced by conducting a survey, while the settlement used non-litigation negotiation theory, with the initial step of making a visit followed by forming a SUS TEAM with the permission of KSPPS NURI JATIM Center.